2020
DOI: 10.1097/ta.0000000000002636
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality, limb loss, and discharge disposition at admission among patients with necrotizing skin and soft tissue infections

Abstract: BACKGROUND Necrotizing soft tissue infections (NSTI) represent a heterogeneous group of rapidly progressive skin and soft tissue infections associated with significant morbidity and mortality. Efforts to identify factors associated with death have produced mixed results, and little or no data is available for other adverse outcomes. We sought to determine whether admission variables were associated with mortality, limb loss, and discharge disposition in patients with NSTI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 26 publications
0
14
1
Order By: Relevance
“…diabetes mellitus, renal failure, history of malignancy) and laboratory results upon presentation (e.g. creatinine, lactate) are frequently reported to be potential predictors for mortality in these patients [ 15 , 24 , 25 ]. Nonetheless, the most important, potentially modifiable predictor for mortality remains time to treatment [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…diabetes mellitus, renal failure, history of malignancy) and laboratory results upon presentation (e.g. creatinine, lactate) are frequently reported to be potential predictors for mortality in these patients [ 15 , 24 , 25 ]. Nonetheless, the most important, potentially modifiable predictor for mortality remains time to treatment [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Dutch healthcare system is constructed in such a way, that it is tempting to speculate that necrotizing fasciitis patients who present to academic hospitals (primarily or secondarily) had more comorbidities, a more severely extended infection (potential due to delay in presentation) and/or had a higher degree of physiological derangement upon presentation warranting a more aggressive surgical approach to obtain source control. A previous meta-analysis showed that treatment delay does not necessarily result in a higher rate of amputations and another study was not able to find a correlate between the amputation rate and specific causative micro-organisms (GAS necrotizing fasciitis vs. necrotizing fasciitis caused by other micro-organisms), however other studies have shown that factors such as sepsis and transfer to another hospital are predictors for amputation as treatment [ 4 , 12 , 15 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to previous studies, polymicrobial infection was still the predominant type of NF worldwide and, in addition known as type I NF ( Giuliano et al, 1977 ;Hagedorn and Wessells, 2017 ;Horn et al, 2020 ;Rahim et al, 2019 ;Tang et al, 2015 ). Apart from presenting typical symptoms like erythema, swelling, pain and systemic fever, type I NF was more likely to encounter specific signs, including crepitus and gassy manifestation in the affected region resulting from a mixed-infection of both aerobes and anaerobes ( Huang et al, 2020aLiu et al, 2005 ).…”
Section: Discussionmentioning
confidence: 98%
“…Efforts to differentiate and predict adverse outcomes need to encompass many data points including but not limited to laboratory data, comorbidities, infection site, etiology, and treatment regimens used. 7 To this day, no single categorical organization for NSTIs exists; they can be separated into 4 types: type I-polymicrobial/ synergistic, type II-monomicrobial gram-positive (group A Streptococci or Staphylococcus aureus), type III-monomicrobial gram-negatives (typically marine-related organisms, such as Vibrio vulnificus), and type IV-fungal. Type I is the most common, accounting for 80% of the cases, followed by type II, which accounts for 10%-15% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Amputation rates in previous studies ranged from 14% to 26%. 7,11,[15][16][17] Some of the variables identified that were associated with increased amputation risk were older than 60 years, diabetes, sepsis, systolic blood pressure less than 90 mm Hg at admission, heart disease, transfer status, chronic wound as etiology, sodium less than 130 mEq/L, male sex, and non-White ethnicity. 11,12,18 Jansen-Winkeln et al 3 found the diagnosis of NSTI primarily clinical and that a regimen of clindamycin, gentamicin, and penicillin provides satisfactory coverage against 95% of causative pathogens.…”
Section: Discussionmentioning
confidence: 99%